Original article Mixed cryoglobulinaemia: demographic, clinical and serologic features in 16 patients - Kamińska, Karolina; Czubek, Maria; Szczerkowska-Dobosz, Aneta; Wilkowska, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Cryoglobulins are proteins, from the group of immunoglobulins, that precypitate below 37 o C and redissolve on rewarming. Cryoglobulinaemias are systemic diseases characterized by presence of cryoglobulins in the serum and classified according to their types. They lead to systemic vasculitis involving mostly small, but sometimes larger vessels, causing multiple organ involvement, and can be associated with variety of clinical conditions including chronic infections, inflammatory and lymphoproliferative disorders, autoimmune disorders, myeloma, macroglobulinaemia, etc. The study investigated the demographic, clinical and serological features and treatment outcome in 16 cryoglobulinaemia cases within a group of patients hospitalized in the Department of Dermatology, Venerology and Alergology of the Medical University of Gdańsk between years 2000 and 2005.